Hama Jagung Di Gudang Penyimpanan Dengan Kadar Air Berbeda - susiana, Lilis; Pramudi, Muhammad Indar; Rosa, Helda Orbani (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
This research aims to determine pests in feed corn at several moisture levels in storage warehouses developed in Tirta Jaya Village, Bajuin District, Tanah Laut Regency and PT Arutmin Site Satui, Tanah Bumbu Regency. Sampling at two locations was carried out directly at the farmer's corn storage warehouse and PT Arutmin Site Satui, at the Tirta Jaya Village location 4 kg samples were taken and at the PT Arutmin Site Satui location 3 kg samples were taken, then each sample was weighed weighing 300g each with 3 repetitions, and stored for 1 month. The warehouse pest data obtained will be grouped based on water content, varieties and pests obtained in 1 table. Next, the number of warehouse pest populations is calculated, the population average is calculated, the damage intensity is calculated, the data is tabulated and analyzed descriptively. The observation results showed that the Bisi 2 variety had the highest population of warehouse pests and the intensity of damage with a population of 143 Doloessa viridis, Tribolium sp. 58 individuals, 242 larvae and 11 pupae, with the highest average damage intensity reaching 34.6%. Meanwhile, the warehouse pest population and intensity were the lowest in the RK 457 variety with a total population of Tribolium sp. 8 tails with damage intensity reaching 8%.